A new candidate vaccine for human brucellosis based on influenza viral vectors: a preliminary investigation for the development of an immunization schedule in a guinea pig model - Dina Bugybayeva; Zhailaubay Kydyrbayev; Nadezhda Zinina; Nurika Assanzhanova; Bolat Yespembetov; Yerken Kozhamkulov; Kunsulu Zakarya; Sholpan Ryskeldinova; Kaissar Tabynov (BMC, 2021)
Abstract Background A new candidate vector vaccine against human brucellosis based on recombinant influenza viral vectors (rIVV) subtypes H5N1 expressing Brucella outer membrane protein (Omp) 16, L7/L12, Omp19 or Cu-Zn SOD proteins has been developed. This paper presents the results of the study of protection of the vaccine using on guinea pigs, including various options of administering, dose and frequency. Provided data of the novel vaccine candidate will contribute to its further movement into the preclinical stage study. Methods General states of guinea pigs was assessed based on behavior and dynamics of a guinea pig weight-gain test. The effectiveness of the new anti-brucellosis vector vaccine was determined by studying its protective effect after conjunctival, intranasal and sublingual administration in doses 105 EID50, 106 EID50 and 107 EID50 during prime and boost vaccinations of animals, followed by challenge with a virulent strain of B. melitensis 16 M infection. For sake of comparison, the commercial B. melitensis Rev.1 vaccine was used as a control. The protective properties of vaccines were assessed by quantitation of Brucella colonization in organs and tissues of infected animals and compared to the control groups. Results It was observed a gradual increase in body weight of guinea pigs after prime and booster immunization with the vaccine using conjunctival, intranasal and sublingual routes of administration, as well as after using various doses of vaccine. The most optimal way of using the vaccine has been established: double intranasal immunization of guinea pigs at a dose of 106 EID50, which provides 80% protection of guinea pigs from B. melitensis 16 M infection (P < 0.05), which is comparable to the results of the effectiveness of the commercial B. melitensis Rev.1 vaccine. Conclusions We developed effective human vaccine candidate against brucellosis and developed its immunization protocol in guinea pig model. We believe that because of these studies, the proposed vaccine has achieved the best level of protection, which in turn provides a basis for its further promotion.